Decolonizing Librarians’ Teaching Practice: In Search of a Process and a Pathway - Laverty, Corinne; Berish, Francine (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2022)
Many educators across post-secondary institutions are learning about their colonial histories and the need to decolonize curriculum, learning materials, and teaching practice described in the Truth and Reconciliation Commission of Canada: Calls to Action (2015). This qualitative study explored the meaning of decolonizing with a group of ten instruction librarians at a mid-sized Canadian institution. The project was conducted in the form of a learning program to offer the predominantly white settler librarian participants a chance to explore these topics. It provided an opportunity to document a learning process and a pathway to initiate change. A five-month learning program uncovered participant questions and interpretations of decolonizing drawing on transcripts of individual learning journals and a focus group as the data set. The program inspired a community of practice enabling the learning and unlearning essential to decolonizing. We report, from the perspective of two white settler librarians, on the meaning of decolonizing as an ongoing process that enables awareness of colonization, personal identity, and positionality and includes strategies librarians can use on the path to decolonizing teaching, collections, and spaces. Participant self-awareness surfaced a critical librarianship mindset where information is understood as a product shaped by cultural, historical, social, and political forces, and where we acknowledge that academic libraries and their information sources and systems are not neutral and empower specific voices.